Microbial Transformation of Prochiral Ketones Using Rhizopus arrhizus - R. SALOKHE, PRABHA; S. SALUNKHE, RAJESHRI (Asian Journal of Chemistry, 2010)
The various species of Rhizopus arrhizus have been used for microbial transformations of p-chloro, p-methyl and p-methoxy propiophenone to synthesize corresponding enantiomerically pure (S) alcohols in 70- 90 % ee. In a screening of various species of Rhizopus arrhizus for enantioselective reduction of propiophenone derivatives, Rhizopus arrhizus NCIM-878 showed high activity for reduction of above prochiral ketones and it efficiently hydrolyzes the racemic acetate of p-methoxy propiophenone to corresponding (R) alcohol.